Expect the unexpected: a case report on lingual bone perforation during implant placement - Mohd Noh, Nur Zety; Ariffin, Farha (Savvy Science, 2025)
Objective; The incidence of lingual bone perforation during implant placement is lower than that of buccal bone perforation and is rarely reported. This case describes an anatomy related implant complication of a 53-year-old lady during implant placement of 36. Case report; A 3.4mm implant width and 9.5mm implant length with adjunct concentrated growth factor (CGF) were planned for this patient. A full thickness flap was elevated on the edentulous ridge of missing tooth 36. By utilizing the individually constructed surgical stent, the surgery was initiated with a pilot marking drill. The drill angulation was evaluated and an intraoral periapical radiograph was taken. Prior to the implant placement, a careful inspection was conducted on the implant site preparation. However, a lingual bone fenestration was observed. Due to potential complications associated with lingual bone perforation, implant placement was deferred, and a guided bone regeneration procedure was performed. Prior to the flap approximation, a layer of CGF membrane was positioned. Afterwards, the patient was recalled regularly up to one-year post-operative. Following one-year of follow-up, the surgical area healed uneventfully with radiographic evidence of bone formation and maturation. Conclusion; Although a case can be relatively straightforward with proper surgical planning, clinicians need to always be prepared for the unexpected event.